Settlement of Criminal Case of Insultation against Class (Article 156 of the Criminal Code) through the Dayak Ngaju Traditional Court - Dody Heryanto; I Nyoman Nurjaya; Prija Djatmika; Hanif Nur Widhiyanti (Budapest International Research and Critics University, 2022)
Within the Dayak community to resolve a case or dispute, it is often used through the customary court conducted by Damang. Damang is the traditional leader of the kademangan who functions as the customary head. The existence of Damang as a Customary Peace Judge is recognized and obeyed by the Dayak community in Palangka Raya. This study discusses two main problems, namely, first, the Ngaju Dayak customary justice system in resolving cases of insults to groups. Second, the effectiveness of the Ngaju Dayak customary courts in resolving cases of insult to groups can be described as follows: (1) That the Dayak indigenous people have traditionally had a way of settling disputes outside the court (commonly known as Alternative Dispute Resolution, where in resolving cases based on in the results of the peace meeting in Tumbang Anoi 1894, namely 96 articles of Dayak customary law which is an express customary law (geschreven recht) used in the Dayak customary trial in the case of insulting groups carried out by Prof. Dr. Thamrin Amal Tomagola, (2) Legal mechanisms Dayak customs in resolving problems or cases, including cases of humiliation that occur to the Dayak community are in the form of (barunding), consultation (hapakat) and mediation (nyangkelang). The pattern carried out by Damang can be qualified as patterns of mediation settlement. n cases through the Dayak customary court, namely 1) simple, fast and low cost; 2) is voluntary; 3) guarantee confidentiality for each party, 4) more flexible case resolution.